Dietary Advanced Glycation End Products (AGEs) could alter ovarian function in mice. (15th June 2020) - Thornton, Kimberly; Merhi, Zaher; Jindal, Sangita; Goldsammler, Michelle; Charron, Maureen J.; Buyuk, Erkan
Abstract: Nutrition is an important source of exogenous AGEs and thermally processed foods present in western-style diets contain a large amount of these pro-inflammatory AGEs. Additionally, the intake of dietary AGEs could upregulate ovarian gene expression of inflammatory macrophage markers. The objective of this study was to investigate the effect of diet rich in AGEs on estrous cyclicity and ovarian function in a mouse model. Six-week old C57BL/6 J female mice were randomly subjected to either a diet low in AGEs (L-AGE) or a diet high in AGEs (H-AGE) for a total of 13 weeks. Experiments performed included daily vaginal smears to assess estrous cyclicity, ovarian superovulation with gonadotropins to assess the number of oocytes released, whole ovarian tissue mRNA quantification by RT-PCR to quantify genes involved in folliculogenesis, steroidogenesis, and macrophage markers, and ovarian morphology for follicle count. Outcome measures included estrous cyclicity, number of oocytes following superovulation, expression of genes involved in folliculogenesis, steroidogenesis, and macrophage infiltration as well as the number of primordial, primary, secondary, antral follicles and corpora lutea. Compared to mice on L-AGE diet, mice on H-AGE spent significantly longer time in the diestrus phase, had similar number of oocytes released following ovarian superovulation, and showed significant alterations in genes involved in steroidogenesis (increase in Star mRNA expression levels) and folliculogenesis (increase in Gdf-9 and Fshr mRNA expression levels). Mouse macrophage marker F4/ 80 mRNA expression was upregulated in mice on H-AGE diet compared to mice on L-AGE diet. Finally, mice on H-AGE diet had significantly fewer corpora lutea in their ovaries. These results indicate that the ingestion of high amounts of dietary AGEs could disrupt folliculogenesis and steroidogenesis that might lead to abnormal estrous cyclicity. Intake of dietary AGEs could also upregulate ovarian gene expression of inflammatory macrophage markers. Highlights: There was no significant difference in body weight between mice fed L-AGE or H-AGE diet. Mice on H-AGE diet spent significantly longer time in the diestrus phase compared to mice on L-AGE diet. The expression the macrophage marker F4/80 is significantly increased in the ovaries of mice on H-AGE diet. Mice on H-AGE diet had a significant increase in ovarian Gdf-9 and Fshr mRNA expression compared to mice on L-AGE diet.